Freshwater crabs of Gunung Singai, Sarawak: diversity and potential criteria for integrated water catchment management policies - Jongkar, Grinang (2012)
Integrating biological diversity into water catchment management policies has the potential to enhance our understanding of the complexity of interrelationships between organisms and environment and contribute to wise utilization of natural resources. In the case of Sarawak’s Gunung Singai, a two-year study found that freshwater crabs have potential to be incorporated into water catchment management policies in the area. First, in terms of conservation value, freshwater crabs of Gunung Singai are fairly diverse, consisting 10 species, all of which are endemic to Borneo, and two (Ibanum pilimanus & Isolapotamon bauense) classified as ‘Threatened’ in IUCN Red Lists. Secondly, the distribution structure of freshwater crabs on Gunung Singai is strongly correlated to habitat types and seasons. Some species are widely distributed across the water catchment area, but a few tend to be restricted in habit use (I. bauense, I. collinsi, I. doriae & Terrathelphusa kuchingensis). Three semi-terrestrial species were also found in the area, either in holes at localized sites or under leaf litters. The study found that semi-terrestrial species were commonly encountered during the rainy season. Thirdly, from an ecological perspective, freshwater crabs play important roles in nutrient cycling and also as prey to larger animals. The presence of freshwater crabs in streams in large number can help maintaining the integrity of the ecosystem. Ethnozoological value are insignificant in the area, but consuming freshwater crabs (I. bauense) had been practiced in the past, and are occasionally harvested at present. Considering these important attributes, integrated management of water catchment in Gunung Singai in the future need include freshwater crabs as one of biological parameters